(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2007)
ABSTRACT : It is perceived that psychological benefits motivate people to seek outdoor experiences in addition to social and biological benefits. Individual needs are usually influenced by one’s socio-demographic situation, past experience, personal attitudes and values among other factors. In this study, a survey was conducted that assessed individual perception and satisfaction of hiking activities (n=146). Enjoying nature and escaping from physical pressure are the most important outcomes perceived by respondents whereas developing leadership skills and family togetherness are least important. Paired t-test determined that a significant proportion of respondents were not satisfied with their needs for enjoyment. Implications of unsatisfactory experience in relation to environmental, personal and other factors are discussed. Five subgroups of participants in hiking activities among the respondents were identified as: 1) low demand on all benefits; 2) inactive youngsters; 3) young working adults with diverse interests; 4) active naturalists; and 5) well-educated working class, enthusiastic hikers. Furthermore, age is not the most significant factor in this analysis, instead, socioeconomic status and trip related factors highly contributed to the classification. The perception of psychological benefits also varied across the subgroups. Their roles, changes and prospects are also discussed based on the research findings. BENEFICIOS PERCEBIDOS DA CAMINHADA COMO UMA ATIVIDADE DE RECREAÇÃO EXTERNA EM HONG KONG RESUMO: Observa-se que aspectos psicológicos motivam as pessoas a buscarem experiências externas em adição aos benefícios sociais e biológicos. Necessidades individuais são geralmente influenciadas pela situação sócio-demográfica de cada um, experiências passadas, atitudes pessoais e valores entre outros fatores. Nesse estudo, uma pesquisa foi realizada avaliando a percepção individual e a satisfação de atividades de caminhada (n=146).